PENGARUH PENGAWASAN PIMPINAN DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA MELALUI KEPUASAN KERJA PEGAWAI PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA MALANG - Amalia, Rizqi Desi; Samiadji, Samiadji; Limgiani, Limgiani (Magister Manajemen Universitas Wisnuwardhana, 2020)
The purpose of this study was to analyze the influence of supervisory leadership, work motivation, and job satisfaction that contribute simultaneously and significantly to the work discipline of PDAM Malang City employees. In accordance with the main problem and research objectives that have been formulated, this type of research is quantitative research. The sample in this study were 188 employees of PDAM Malang City. The population in this study were 353 people . The data analysis method used is path analysis. Based on data analysis, there is evidence that leadership supervision and work motivation have a simultaneous and significant effect on job satisfaction, leadership supervision, work motivation, and job satisfaction simultaneously and significantly affect work discipline, and leadership supervision and work motivation simultaneously and significantly affect work motivation. work discipline through job satisfaction.